PENINGKATAN PENGENALAN KONSEP ANGKA MELALUI PERMAINAN KALENDER DI TAMAN KANAK-KANAK ISLAM SILATURAHMI KABUPATEN PADANG PARIAMAN - Nurmainis, Nurmainis (Universitas Negeri Padang, 2012)
The background of this research because of the low number of children in the introduction of the concept of symbol numbers and understanding the concept of numbers. This is because the purpose of this research is to improve the concept of numbers through the game calendar in B1 group Islamic Kindergarten Gathering Pariaman district. Type of research is Classroom Action Research (CAR), Data collection techniques were observation and documentation. Data analysis techniques using percentages. Action research was conducted in two cycles, each cycle conducted three meetings.